Maritime Archaeology and Underwater Cultural Heritage in the Disputed South China Sea. Issue 3 (20th December 2018) - Perez-Alvaro, Elena; Forrest, Craig
Abstract: China's broad geopolitical strategy and positioning for global influence includes its averred legal position in relation to its sovereignty and jurisdiction in the South China Sea. A response to this legal position was the Philippines' initiation of arbitral proceedings constituted under the United Nations Convention on the Law of the Sea. Despite the non-participation of China in these proceedings, the arbitral decision of 2016 clarified a number of legal provisions pertinent to the ongoing territorial and maritime disputes in the South China Sea. This decision impacted directly on China's assertion of sovereign and jurisdictional historical title or rights, which, in part, relies on evidence obtained from underwater cultural heritage and the associated maritime archaeology. This article critically evaluates China's maritime archaeology program and its policy with respect to underwater cultural heritage in light of the 2016 arbitral decision and the underlying international law of the sea. While recognizing that China's policy is not inconsistent with its broader heritage policy, and its national approach to the protection of underwater cultural heritage, this article argues that this cannot be used to support China's South China Sea claims and is not only misplaced, such as to pose a risk to the archaeological record, but also inconstant with international developments in the form of the 2001 United Nations Convention of the Protection of the Underwater Cultural Heritage.